Bumble bee nest thermoregulation: a field study. Issue 3 (27th May 2023) - Gradišek, Anton; Bizjak, Jani; Popovski, Aleksej; Grad, Janez
Abstract: Careful control of brood temperature is important for successful colony development in social insects. Six bumble bee colonies of six common Central European species ( B. hypnorum, B. hortorum, B. argillaceus, B. pascuorum, B. humilis, B. sylvarum ) were continuously monitored for several weeks. We recorded the brood temperature as well as the air temperature in the nest and outside once per minute using a homemade electronic setup. Two colonies succeeded in producing new queens and males during the measurement period while the other four colonies were attacked by parasites at some point during the equilibrium stage. We discuss the nest thermoregulation in view of species and the number of workers in the colony. The results show that the strongest colonies were able to maintain very stable brood temperature over longer periods (standard deviations below 0.5 °C), which is in agreement with previous studies. Colonies with 25 or more workers typically kept the standard deviation below 1 °C. There are two main contributions to the paper. First, we discuss the applicability of a multi-sensor monitoring setup for an outdoor study. Second, due to fast temperature sampling, we were able to observe different thermoregulation strategies that colonies may apply, including keeping the temperature above 31 °C at night and letting it rise during the day in B. argillaceus and short heating cycles in B. sylvarum .